IMPLEMENTASI VERNAM CIPHER UNTUK PENGAMANAN FILE TEKS - Jeita Parulian Pinem; Zekson Arizona Matondang (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2018)
One of the security processes that can be applied in the process file storage is to do the cryptographic process. The cryptographic process is carried out by randomizing the data, so that the original file is not easy to read by unauthorized parties. . The Vernam Cipher method is a symmetric key type algorithm, which is a key used to encrypt and decrypt using the same key. In the encryption process, the Vernam Cipher algorithm uses a stream cipher where the cipher is derived from the XOR results between the plaintext bit and the bit key. This research will discuss the cryptographic process of a text file. The cryptographic process consisting of encryption and decryption will use the Vernam Cipher method.